EFFECT OF A SHORT PERIOD WHOLE BODY VIBRATION WITH 10 HZ ON BLOOD BIOMARKERS IN WISTAR RATS - Monteiro, Milena de Oliveira Bravo; Sá-Caputo, Danúbia da Cunha de; Moreira-Marconi, Eloá; Frederico, Éric Heleno Freire Ferreira; Sousa-Gonçalves, Cintia Renata de; Bernardo, Luciana Camargo; Guimarães, Carlos Alberto Sampaio; Bernardo-Filho, Mario (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Exposure to whole body vibration exercises (WBVE), besides some biological effects, causes alterationsin the concentration of some blood biomarkers. The aim of this study is to evaluate the action of vibration (10 Hz) ofWBVE on the concentration of blood biomarkers in Wistar rats.Materials and Methods: Wistar rats were divided in 2 groups. The experimental group (EG) was subjected tovibrations of 10Hz (one min per day, one week, total time of seven min), while the control group (CG) has notexperienced vibration. Samples of whole blood were drawn for biochemical analysis of the concentration of totalcholesterol, triglycerides, HDL, LDL, VLDL, glucose, CPK, albumin, alkaline phosphates, TGP, TGO, γGT, lipase,amylase, urea and creatinine.Results: White blood cell count and a platelet-hemogram were also performed. Significant (p<0.05) increase in TGP,TGO and white blood cells and decrease in LDL concentration was found after exposure of 10Hz mechanical vibration.Conclusion: Although these findings were obtained with rats, they might contribute to try to understand better thesemechanisms that occur following exposure to a frequency of 10Hz.